Trocas gasosas e características produtivas de plantas de soja expostas ao solo encharcado e restrição luminosa - Cecatto Junior, Roberto (2024)
Soybean plants exposed to waterlogged soil have hypoxic root tissues with low oxygen content, which leads to a reduced rate of aerobic respiration and greater anaerobic activity, generating metabolic disorders that affect leaf gas exchange and photosynthetic activity, impairing growth and production. Another condition that is harmful to the plant consists of periods with restricted incident light due to excessive cloudiness, which negatively affects gas exchange and the functioning of the photosynthetic apparatus. Thus, this study aimed to investigate leaf gas exchange, leaf chlorophyll and nutrient contents, photosynthetic activity, growth and production of soybean plants exposed to soil waterlogging and light restriction in the vegetative and reproductive phases. The study evaluated the following treatments: plants in control condition, plants with light restriction, plants in waterlogged soil, and plants in waterlogged soil with light restriction. Two experiments were conducted. In the first, the treatments were applied simultaneously at the beginning of the V5 phenological stage (experiment 1) and in the second experiment, the treatments were applied simultaneously at the beginning of flowering (R1) (experiment 2). To impose the restriction of incident light, a shading screen with the capacity to retain 80% of the incident light was used. Treatments in waterlogged soil were carried out keeping the soil above field capacity. Leaf gas exchange and relative chlorophyll content were determined five and ten days after the treatments were applied. Gas exchange every two hours throughout the day, chlorophyll content, specific leaf area and response curves of the net assimilation rate of CO2 as a function of the flux density of photosynthetically active photons were determined 7 and 14 days after the treatments were applied. Biometric evaluations and determination of leaf nutrient content were performed 14 days after the start of the treatments. At the end of the crop cycle, the production components and production per plant were evaluated. Exposure to waterlogged soil and light restriction, alone or together, from the V5 or R1 phenological stages, provided a lower rate of net CO2 assimilation related to the reduction of stomatal opening and decline in transpiration, at five and ten days of exposure to stress conditions. Plants exposed for 7 and 14 days to soil waterlogging and light restriction, alone or together, from the vegetative or reproductive phase, showed a reduction in the rate of net CO2 assimilation associated with lower stomatal opening and reduced leaf transpiration throughout the day. Plants under light restriction showed an increase in specific leaf area, chlorophyll content and apparent quantum efficiency, which are related to the decrease in the rate of net CO2 assimilation under reduced light. Plants in waterlogged soil under full sunlight presented chlorotic leaves with lower nitrogen, phosphorus, and potassium contents and lower apparent quantum efficiency, which probably contributed to the reduction in the net photosynthetic rate. The declines in the net CO2 assimilation rates of plants exposed to waterlogged soil and under light restriction, from the V5 or R1 phenological stages, are correlated and resulted in a decrease in dry mass accumulation, number of pods per plant, and grain production. Therefore, exposure to waterlogged soil and light restriction, alone or together, negatively interfere with gas exchange, photosynthetic activity, dry mass accumulation, and grain production of soybean plants.